2021
DOI: 10.1016/j.jchf.2020.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and Mechanistic Analysis of Spironolactone in Patients at Risk for HF

Abstract: Background: Further to their beneficial effects in established heart failure (HF), mineralocorticoid receptor antagonists may act upstream on mechanisms preventing incident HF. In people at risk for developing HF, the "Heart OMics in Aging" (HOMAGE) trial showed that spironolactone treatment could provide antifibrotic and anti-remodelling effects, potentially slowing the progression to HF.Objectives: To further understand the mechanisms underlying spironolactone effect, we assessed its impact on multiple plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 29 publications
3
56
2
Order By: Relevance
“…It may therefore be speculated that spironolactone mediates distinct beneficial effects in HFpEF by enhancing ADM and GH expression. The increase in MMP7 plasma levels observed in our study is consistent with recent findings demonstrating a similar regulation through spironolactone in a cohort of patients at risk of developing HF (HOMAGE trial) [12]. Interestingly, plasma levels of MMP7 were also reported to be increased in patients with diastolic HF [45].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It may therefore be speculated that spironolactone mediates distinct beneficial effects in HFpEF by enhancing ADM and GH expression. The increase in MMP7 plasma levels observed in our study is consistent with recent findings demonstrating a similar regulation through spironolactone in a cohort of patients at risk of developing HF (HOMAGE trial) [12]. Interestingly, plasma levels of MMP7 were also reported to be increased in patients with diastolic HF [45].…”
Section: Discussionsupporting
confidence: 92%
“…The analysis of large panels of plasma or serum biomarkers in distinct patient cohorts is a common approach in cardiovascular science [11][12][13]. It can be used to identify underlying mechanisms of the disease of interest, or to analyse downstream effects of an administered drug.…”
Section: Introductionmentioning
confidence: 99%
“…Spironolactone did not significantly change the proteomic profiles of patients with diabetes, but yielded the same clinical benefits as in the complete HOMAGE cohort. The four proteins which were significantly modified in diabetic patients after 9 months of spironolactone treatment (COL1A1, PICP, SELE and MMP7) are altered in the same direction as in the complete population, indicating that the effects are not specific for diabetic patients [ 9 ]. These proteins are implicated in extracellular matrix metabolism (COL1A1, PICP), cell-cell adhesion (SELE) and proteolysis (MMP7).…”
Section: Discussionmentioning
confidence: 99%
“…As spironolactone is a steroidal mineralocorticoid receptor antagonist (MRA) that is not specific for the mineralocorticoid receptor, it may exert other effects (e.g., cortisol elevation) on glucose and insulin metabolism. In a previous analysis we showed the influence of spironolactone on the proteome in the total HOMAGE trial population [ 9 ]. It remains unknown to what extent DM influences the effects of spironolactone on clinical and proteomic variables.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies investigating the potential underlying mechanisms of MRA therapy in HF, demonstrated receptormediated effects in cardiomyocytes and vascular endothelial cells, which was independent of simple diuretic effects mediated by mineralocorticoid receptor activation in the kidneys [8][9][10]. An exploratory analysis from the HOMAGE trial using targeted proteomics has found evidence of the spironolactone exerting pleiotropic effects across multiple mechanistic pathways, spanning the mitigation of fibrosis, thrombosis, congestion, vascular function and inflammation [27].…”
Section: Discussionmentioning
confidence: 99%